2020
DOI: 10.1155/2020/5347828
|View full text |Cite
|
Sign up to set email alerts
|

Academic Burnout and Academic Achievement among Secondary School Students in Kenya

Abstract: The study examined the relationship between academic burnout and academic achievement among secondary school students in the Kenyan context. Data were collected from 714 form 4 students (equivalent to 12th graders) drawn from 31 public secondary schools. The Maslach Burnout Inventory Student Survey was used. Academic achievement was measured using students’ grades in end of term examinations. The results of the Pearson product moment correlation of coefficient revealed a significant inverse relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 9 publications
3
7
0
3
Order By: Relevance
“…In the educational process, someone with a high academic performance score will attain considerable accomplishment (Susanti, 2019). This situation different with students in a state of academic burnout who will exhibit several undesirable behaviors, such as having an excessive workload, a lack of interest in learning, and a reluctance to engage in activity learning, all of which contribute to a decline in academic performance (Oyoo et al, 2018). Academic burnout is associated with a lack of problem-solving skills among students with a negative mindset.…”
Section: Resultsmentioning
confidence: 99%
“…In the educational process, someone with a high academic performance score will attain considerable accomplishment (Susanti, 2019). This situation different with students in a state of academic burnout who will exhibit several undesirable behaviors, such as having an excessive workload, a lack of interest in learning, and a reluctance to engage in activity learning, all of which contribute to a decline in academic performance (Oyoo et al, 2018). Academic burnout is associated with a lack of problem-solving skills among students with a negative mindset.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, low achievers reported more burnout as compared to high achievers at school. In another study conducted in Kenya, Oyoo et al (2020) found a significant negative correlation between academic burnout and academic accomplishment in adolescents as the participants with a lower level of academic burnout had a higher level of academic accomplishment. Interestingly, it was also found that emotional exhaustion and cynicism were not significant predictors of academic success.…”
Section: Introduction and Literature Reviewmentioning
confidence: 88%
“…Since the above-cited studies are found inconclusive, as some of the researchers (e.g., Madigan & Curran, 2021;Oyoo et al, 2020) found emotional exhaustion significantly associated with lower academic performance while some of them (e.g., March-Amengual et al, 2022) found no significant association between these constructs. Moreover, there is also a need to add empirical findings to the existing body of indigenous literature to determine the relationship between these constructs.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…In addition, being proactive when setting goals and deploying strategies to regulate one's knowledge is difficult if the degree of burnout is high (Oyoo et al 2020). This sensation of exhaustion may respond to the pressure exerted upon the learner by the demands of the language-what Schaufeli et al label as "emotional exhaustion" (2002).…”
Section: Research Hypothesesmentioning
confidence: 99%